Case report: The spectrum of SMPD1 pathogenic variants in Hungary - Molnar, Maria Judit; Szlepak, Tamas; Csürke, Ildikó; Loth, Szendile; Káposzta, Rita; Erdős, Melinda; Dezsőfi, Antal (Frontiers in Genetics, 2023)
Acid sphingomyelinase deficiency (ASMD) is an autosomal recessive disease caused by biallelic pathogenic variants in the sphingomyelin phosphodiesterase‐1 (SMPD1) gene. ASMD is characterized by a spectrum of disease and is broadly divided into three types (ASMD type A, ASMD type A/B, and ASMD type B). More than 220 disease-associated SMPD1 variants have been reported, and genotype/phenotype correlations are limited. Here we report the first description of all six diagnosed ASMD cases in Hungary. Nine SMPD1 variants are present in this cohort, including 3 SMPD1 variants (G247D, M384R, and F572L), which have only been described in Hungarian patients. All described variants are deemed to be pathogenic. Eight of the variants are missense, and one is a frameshift variant. The treatment of an ASMD type A/B patient in this cohort using hematopoietic stem cell transplantation is also detailed. This study may help to support diagnosis, patient genetic counseling, and management of ASMD.